Majdi Bou-Matar’s Impact: An Examination of the IMPACT Festival and its Survival in the Waterloo Region - Houston, Andrew (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (Graduate Centre for the Study of Drama, University of Toronto, 2019)
The IMPACT Festival is an event dedicated to theatre that centralizes marginalized voices to address social issues, and in the process, works to constitute a vibrant intercultural community. At once a festival, a conference, and an opportunity for artists, scholars, and other cultural commentators—from international to local—to meet and engage with one another, IMPACT has happened biannually in Kitchener, Ontario since 2009. Yet despite its award-winning status among scholars and artists, the IMPACT Festival has struggled to be embraced by either the City of Kitchener or the citizens of the Region of Waterloo. Beginning with interviews with local theatre creators, and drawing on the intercultural analysis of Ric Knowles and Bruno Latour, among others, this article is an attempt to understand why the IMPACT Festival has encountered obstacles to sustainable success in its home town.